Tackling ‘Big’ questions at the bioscience-Islam interface: reporting on the efficacy of an educational programme designed for Muslim high school students - M.Yunus, Raudah (Taylor & Francis, 2024)
‘Big Questions’ about the human being regarding its origin, nature, malleability, culpability and uniqueness lie at the core of the religion-science dialogue. Modern science discoveries have spurred Muslim intellectuals and students to grapple with these fundamental questions anew. In this study, we measured the efficacy of a novel curriculum at the intersection of bioscience and Islam tailored for American Muslim high school students. The educational intervention comprised seven seminars, each developed and delivered by a bioscientist-theologian dyad. Outcome measures, based on the Kilpatrick’s Evaluation model were: (a) knowledge; (b) participant interest, intention, and preparedness to learn, engage with, and pursue opportunities at this intersection; and (c) opinion/belief about science-religion compatibility. Our seminars positively impacted participant knowledge and preparedness (knowledge: pre = 14.7, post = 18.6, p = <0.01, preparedness: pre = 10.8, post = 12.8, p <0.01). There was no change in aggregate participant interest, intention and opinion/belief pre- and post-intervention (interest: pre = 51.2, post =50.6, p = 0.35, intention: pre = 18.7, post = 18.5, p =0.74, opinion: pre = 42.5, post = 41.1, p = 0.12). Baseline interest independently predicted knowledge gain (B: 0.68, 95%CI: 0.13, 1.23, p = 0.02), while lower baseline knowledge predicted improvement in preparedness (B: −0.07, 95%CI: −0.13, −0.01, p = 0.02). We encourage researchers and educators to continue exploring ways to build stable professional identities among students with religious orientations at the science-religion intersection.